2021
DOI: 10.3390/jtaer16010001
|View full text |Cite
|
Sign up to set email alerts
|

Young Generation’s Mobile Payment Adoption Behavior: Analysis Based on an Extended UTAUT Model

Abstract: Younger generations comprise an essential segment for the mobile payment market to prosper. However, empirical evidence of the drivers/barriers of the young generation’s adoption of mobile payment has been inconclusive. This study intends to advance the body of knowledge on this subject based on the extended Unified Theory of Acceptance and Use of Technology (UTAUT), incorporating the young generation’s risk perception and bonus/rewards provided by the mobile-pay firms. To this end, 295 samples with the majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…While consumers would enjoy price discounts and have better experiences from digital wallets, merchants would benefit from higher sales volume and lower marketing expense. Many studies confirmed the positive influence of promotion on BI (Wei et al, 2021).…”
Section: Promotionmentioning
confidence: 85%
“…While consumers would enjoy price discounts and have better experiences from digital wallets, merchants would benefit from higher sales volume and lower marketing expense. Many studies confirmed the positive influence of promotion on BI (Wei et al, 2021).…”
Section: Promotionmentioning
confidence: 85%
“…We selected the control variables, drawing on the existing literature on mobile payment adoption (e.g., Moorthy et al, 2020; Wei et al, 2021; Zhao & Zhao, 2022; Zhao, Wu, & Guo, 2022; Zheng & Ma, 2021), household expenditures (Chang et al, 2022; Eika et al, 2020; Zhu et al, 2021), and subjective wellbeing (Dufhues et al, 2023; Ma, Vatsa, & Zheng, 2022; Ugur, 2021). Specifically, the variables representing age, gender, education levels, marital status, trust perception, household size, investment activity, car ownership, social interaction, internet penetration rate, urban (versus rural), and geographical location were included as control variables in the empirical analysis.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…The results indicate that apart from the social influence performance expectancy plays a crucial role in the adoption of digital payment systems. Wei et al [38] study was undertaken to determine the acceptance of mobile payment by retailers. There were several factors which were scrutinized regarding their significance in the adoption of mobile payment apps.…”
Section: Introductionmentioning
confidence: 99%